Acceptability of bonbons made with camu-camu (Myrciaria dubia L) - Grigio, Maria Luiza; Chagas, Edvan Alves; Berlingieri Durigan, Maria Fernanda; Cardoso Chagas, Pollyana; Moura, Elias Ariel; Ferreira Carvalho, Gabriella; Zanchetta, Jayne Julia; Marques Silva, Caroline; Cabral , Victor Braz; Queiroz Costa, Érica Catrine; Rodrigues Oliveira, Railin (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
The aim of this study was to formulate and evaluate different formulations of camu-camu bonbons, verifying which formulations obtained greater acceptability and maintenance of their nutraceutical potential. The bonbons were made of 2 chocolate-based toppings (white chocolate and milk chocolate), with three types of camu-camu-based fillings (candy, candy + jelly and candy + syrup). A sensory analysis was performed using a questionnaire and a hedonic scale ranging from 9 to 1 to evaluate appearance, colour, taste and texture. The hedonic scale used to assess purchase intentions ranged from 5 to 1. The physicochemical characteristics and bioactive compounds of the bonbons were evaluated. Bonbons had excellent acceptability rates, where consumers would definitely buy bonbons: white chocolate stuffed with camu-camu candy+camu-camu syrup (F3) and milk chocolate stuffed with camu-camu candy (F4). Consumers would ‘probably buy’ white chocolate stuffed with camu-camu candy (F1) based on its texture and high levels of vitamin C (VitC), antioxidant activity (FRAP) and (DPPH), phenolic compounds (Phen), and flavonoids (Flavon). Milk chocolate stuffed with camu-camu candy (F4), white chocolate stuffed with camu-camu candy+camu-camu syrup (F3), and white chocolate stuffed with camu-camu candy (F1) have excellent purchase percentages and levels of VitC, FRAP and DPPH, Phen, and Flavon, and especially titratable low acidity; these formulations are highlighted among consumers. Highlights: Camu-camu bonbons have bioactive compounds and high nutraceutical potential. Different bonbon formulations affect the profile of bioactive compounds in bonbons. The different parts of the camu-camu fruit used in the bonbon’s formulation influence the nutraceutical potential of the products.